On the application of strong approximation to weak convergence of products of sums for dependent random variables - Matuła, P.; Stępień, I. (Condensed Matter Physics, 2008)
We present the application of the strong approximation theorems to the study of weak convergence of products of sums of positive random variables. We focus our attention on sequences of dependent random variables such as associated and mixing sequences.